2021
DOI: 10.1126/science.aax9050
|View full text |Cite
|
Sign up to set email alerts
|

Hunting the eagle killer: A cyanobacterial neurotoxin causes vacuolar myelinopathy

Abstract: Vacuolar myelinopathy is a fatal neurological disease that was initially discovered during a mysterious mass mortality of bald eagles in Arkansas in the United States. The cause of this wildlife disease has eluded scientists for decades while its occurrence has continued to spread throughout freshwater reservoirs in the southeastern United States. Recent studies have demonstrated that vacuolar myelinopathy is induced by consumption of the epiphytic cyanobacterial species Aetokthonos hydrillicola growing on aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 83 publications
0
102
1
Order By: Relevance
“…An example of a recently discovered toxin with (yet) regionally limited occurrence is aetokthonotoxin, a polybrominated tryptophane derivative that is suspected to be the cause of the death of bald eagles and water birds in the United States [211]. Brominated metabolites are known primarily from marine cyanobacteria [212] while halogenated metabolites in freshwater cyanobacteria are generally chlorinated [213].…”
Section: Can We Expect New Cyanobacterial Toxins In the Future?mentioning
confidence: 99%
“…An example of a recently discovered toxin with (yet) regionally limited occurrence is aetokthonotoxin, a polybrominated tryptophane derivative that is suspected to be the cause of the death of bald eagles and water birds in the United States [211]. Brominated metabolites are known primarily from marine cyanobacteria [212] while halogenated metabolites in freshwater cyanobacteria are generally chlorinated [213].…”
Section: Can We Expect New Cyanobacterial Toxins In the Future?mentioning
confidence: 99%
“…The disease was associated with exposure to Hydrilla , and epiphytic cyanobacteria present on the surface of this plant were considered as potential causative agents [ 73 ]. Feeding test animals extracts of certain collections of Hydrilla resulted in gross pathology consistent with AVM, and epiphytic cyanobacteria were also shown to be toxic to bird species such as coots that were fed these extracts [ 74 ]. Extensive research has now identified a brominated cyanobacterial toxin, aetokthonotoxin, which results in the production of vacuoles and lesions in the brains of birds fed this toxin, consistent with it being a cause of AVM [ 74 ].…”
Section: Toxins That Affect the Brain And Nervesmentioning
confidence: 99%
“…Aetokthonotoxin (AETX) is a pentabrominated biindole alkaloid produced by the cyanobacterium Aetokthonos hydrillicola , which grows epiphytically on an invasive plant, Hydrilla verticillata , in freshwater lakes [1] . The toxin traverses the food chain from animals consuming the plant (and thus also the cyanobacterium) like waterfowl or snails and then on to raptors such as eagles (e. g. American bald eagle) and kites.…”
Section: Figurementioning
confidence: 99%
“…The toxin traverses the food chain from animals consuming the plant (and thus also the cyanobacterium) like waterfowl or snails and then on to raptors such as eagles (e. g. American bald eagle) and kites. While the mode‐of‐action of AETX is still unknown, it has been shown to elicit Vacuolar Myelinopathy in birds, which is characterized by a widespread vacuolization of the myelinated axons in the white matter of the brain and spinal cord of affected animals [1] . AETX has also been found to be highly toxic to the nematode C. elegans (LC 50 40 nM), [1] but susceptibility of mammals to this toxin has not been studied, yet.…”
Section: Figurementioning
confidence: 99%